Novel micro-ring structured ZnO photoelectrode for dye-sensitized solar cell - Hossain, M. F.; Zhang, Z. H.; Takahashi, T. (Nano-Micro Letters, 2010)
The micro-ring like structured zinc oxide (ZnO) film was deposited on SnO2: F coated glass substrate by sol-gel dip-coating technique with 1.0 g polyethylene glycol (PEG) content. The surface morphology of micro-ring structured ZnO film has been confirmed by the scanning electron microscope. This ZnO film is used to fabricate the solar cell with the help of ruthenium based dye and carbon counter electrode. The photoelectric and incident photon-to-current conversion efficiency was 1.17% and 48.4%, respectively. The DSC results have been compared with ZnO films prepared without PEG contents.